Handbook of research on electronic surveys and measurements - Reynolds, Rodney A.; Woods, Robert 1970-; Baker, Jason D. (Gale virtual reference library, 2007)
"This book is the comprehensive reference source for innovative knowledge on electronic surveys. It provides complete coverage of the challenges associated with the use of the Internet to develop online surveys, administer Web-based instruments, and conduct computer-mediated assessments. This combination of how-to information about online research coupled with profiles of specific measures makes it an indispensable reference"--Provided by publisher.